A Near-Real-Time Achromopeptidase-Based Enzyme Assay for Biomonitoring of Zinc Pollution in Kuah's Jetty in Langkawi (Journal of Environmental Microbiology and Toxicology, 2023)
Enzyme-based assay in near-real-time biomonitoring provides high sensitivity to bioavailable contaminants, leading to quick results that support prompt action. It is essential to use this method to reduce pollution in drinking, agriculture and marine waters and protect the health of both humans and animals. This work applies a previously discovered enzyme test in biomonitoring to identify contaminants, particularly zinc, in marine water samples from the Langkawi Island, an island that harbors the UNESCO's Geoforest Park status. We used the achromopeptidase dye binding assay, specifically designed for detecting mercury zinc at levels below one part per million, to identify trace amounts of these metal successfully. The test demonstrated a sensitive, quick, and cost-efficient monitoring method with little inhibition (
Keywords: Inhibitive enzyme assay; Achromopeptidase; Biomonitoring; Zinc; UNESCO Site